Peran Penghindaran Kebangkrutan dalam Mengakselerasi Earning Management - Rahman, Faizal Riza; Prabowo, Janitra (STIE Widya Manggala, 2024)
This study aims to analyze the impact of financial distress on earnings management within companies listed on the Indonesia Stock Exchange (IDX) from 2019 to 2021. Utilizing a purposive sampling technique, the research focuses on 44 companies that are noted for their special status on the IDX. Key control variables examined include company size, leverage, cash flow operations (CFO), growth, profitability ratios (ROA), equity issuance (EISSUE), and debt issuance (DISSUE). The findings reveal that financial distress significantly and negatively influences earnings management, indicating that distressed companies are less likely to engage in manipulative financial reporting. Furthermore, the study identifies that all control variables contribute to a nuanced relationship between financial distress and earnings management. Specifically, variables such as size, CFO, leverage, ROA, EISSUE, and DISSUE exhibit a significant positive impact on earnings management, suggesting that larger companies with higher leverage and profitability are more prone to earnings manipulation. Conversely, the growth variable demonstrates a significant negative effect, implying that companies experiencing growth are less likely to manage earnings. These insights contribute to a deeper understanding of the dynamics between financial distress and corporate financial behavior, offering valuable implications for investors, regulators, and policymakers.